Regulation and Reality: A Legal Analysis of the Phenomenon of Women Headed Households in the Cirebon Industrial Sector - Haz, Aaz Jidatul; Mohd Rozi, Robiatun Adawiyah binti (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2024)
Industrialization brings changes that are not better for the surrounding community, especially women who work and play the role of head of the family. The phenomenon of women family heads can be found in the Cirebon industrial area, which has been present for several years through the National Industrial Policy (KIN) program by the Central Government and the Tambourine Triangle by the West Java Provincial Government. This study aims to explore the phenomenon of female heads of households that develops in line with the growth of industry. This research uses a qualitative approach that is presented with descriptive analysis, while the research data collection method is through interviews with 10 female family head informants who work in various existing industries. The results showed that the Regulation of Law Number 12 of 2003 concerning labor guarantees gender welfare in employment. In addition, Cirebon Regency Regional Regulation Number 4 of 2018 concerning women's empowerment and child protection also accommodates the protection of women as heads of families. On the other hand, reality shows that 70% of informants experience discrimination in job promotions, 80% of informants experience a double burden as breadwinners and housekeepers.